Determination of lead, cadmium and copper in roadside soil and plants in Elazig, Turkey - Bakirdere, Sezgin; Yaman, Mehmet (Springer, 2008)
The concentrations of lead, cadmium and copper in roadside soil and plants in Elazig, Turkey were investigated. Soil samples were collected at distances of 0, 25 and 50 m from the roadside. The concentrations of lead, cadmium and copper were measured by Flame Atomic Absorption Spectrophotometry (FAAS). A slotted tube atom trap ( STAT) was used to increase the sensitivity of lead and cadmium in FAAS. Lead concentrations in soil samples varied from 1.3 to 45 mg kg(-1) while mean lead levels in plants ranged from 120 ng g(-1) for grape in point-4 to 866 ng g(-1) for apple leaves in point-2. Lead analyses showed that there was a considerable contamination in both soil and plants affected from traffic intensity. Overall level of Cd in soil samples lies between 78 and 527 ng/g while cadmium concentration in different vegetations varied in the range of 0.8-98.0 ng g(-1). Concentrations of copper in soil and plant samples were found in the range of 11.1-27.9 mg kg(-1) for soil and 0.8-5.6 mg kg(-1) for plants. Standard reference material (SRM) was used to find the accuracy of the results of soil analyses.
Keywords: cadmium; copper; lead; plant leaves; roadside soil; traffic contamination